Ideas of justice and reconstructions of Confucian justice. Issue 2 (2nd April 2016) - Murphy, Tim; Weber, Ralph
ABSTRACT: Confucianism tends to play only a marginal role in current theorizing about justice, which is a global pursuit dominated by Western theory and its strong tendency to assume that justice refers to some substantive conception of distributive, socioeconomic justice. This article examines and compares reconstructions of Confucian justice by Joseph Chan, May Sim, and Fan Ruiping. Each reconstruction makes reference to both classical and modern Western justice theory and thus each involves a comparative approach; indeed, each reconstruction seeks ultimately, in its own distinctive fashion, to present a version of Confucian justice that is comparable with modern Western justice theory. In this article we assess, critically and comparatively, the tertium comparationis and the arguments in each reconstruction. While our analysis does not wholly endorse any of the reconstructions, it shows that there is a richness and vitality to Confucian justice theory that merits proper consideration in justice theory conceived as a truly global and cosmopolitan discipline.